Relative age effect among U14 football players in Portugal: do geographical location, team quality and playing position matter?. Issue 3 (3rd July 2022) - Almeida, Carlos Humberto; Volossovitch, Anna
ABSTRACT: Background: Relative age effect (RAE) has been found to be particularly pronounced between 13 and 15 years of age in male football. However, the extent to which the phenomenon varies within a country demands a more comprehensive approach. Purpose: To examine the effects of geographical location (north; centre-north; centre-south; south; islands), team quality (top-ranked; middle-ranked; bottom-ranked) and playing position (goalkeeper; defender; midfielder; forward) on the birthdate distribution (Q1: January–March; Q2: April–June; Q3: July–September; Q4: October–December) of U14 Portuguese players selected for the national inter-association tournament Lopes da Silva. Methods: A total of 2, 693 players (mean age: 14.12 ± 0.38 years), selected by the 22 regional football associations for the last seven editions of the tournament (2013–2019), was included in the sample. Results: Chi-square analysis showed a small-to-medium RAE in the U14 cohort compared to the general Portuguese male population ( p < .01). Furthermore, the multinomial logistic regression model revealed that the probabilities of selecting Q1 players (vs. Q4) differed ( p < .01) based on geographical location (increases of 76.3% in the north and 87.3% in the centre-north zone compared to the regional teams from islands) and team quality (increase of 94.6% in top-ranked compared to the bottom-ranked teams). The playing position did not affect the magnitude of RAE. Conclusion: Our findings confirm that besides being present in U14 Portuguese male football, the magnitude of RAE is influenced by demographic factors. This study also supports the notion that coaching staffs tend to choose players based on attributes associated with chronological age, seeking to achieve short-term competitive outcomes.